A Distant Shore - Kingsbury, Karen (Washington Square Press, 2021)
Intro – Title Page – Dedication – Chapter One – Chapter Two – Chapter Three – Chapter Four – Chapter Five – Chapter Six – Chapter Seven – Chapter Eight – Chapter Nine – Chapter Ten – Chapter Eleven – Chapter Twelve – Chapter Thirteen – Chapter Fourteen – Chapter Fifteen – Chapter Sixteen – Chapter Seventeen – Chapter Eighteen – Chapter Nineteen – Chapter Twenty – Chapter Twenty-One – Chapter Twenty-Two – Chapter Twenty-Three – Chapter Twenty-Four – Seven Years Later: Chapter Twenty-Five – Acknowledgments – Reading Group Guide – You Were Seen Movement – One Chance Foundation – Real-Life Police Officers – About the Author – Copyright.
Description based on publisher supplied metadata and other sources
Keywords: Intelligence officers-United States-Fiction; Life change events-Fiction; United States-Federal Bureau of Investigation-Officials and employees-Fiction; Intelligence officers; Life change events; Forced marriage; Drug traffic; Human trafficking; Rescues; Electronic books; Employees; novels; Novels; Thrillers (Fiction); Romance fiction; Fiction; Christian fiction; Romantic suspense fiction; Romans